Vocabee: Empowering Language Learning Through Descriptive Text - A Novel Approach to Vocabulary Instruction - Anggriani, Widia; Ikhsanudin, Ikhsanudin; Rezeki, Yanti Sri (Journal of English Education Program, 2023)
This research was conducted to design Vocabee as a teaching and learning media to teach Vocabulary to the eighth-grade students of SMP Negeri 5 Hulu Gurung. The form of this research was Design and Development. This design dan development research was conducted to produce innovative teaching media. The method of this research was adapted from Branch (2009), that consists of three phases namely analyzing, designing, and developing. In the Analyze phase found that the actual conditions of students and the teacher. Design phase was done to prepare the appropriate material to create the application. Develop phase was done to create an essential part of the Vocabee using software called Articulate Storyline 3. The designed product was completed after have an expert validation regarding to the needs and already valid to be use by expert validator. As the result, Vocabee is useable to support the process of teaching and learning vocabulary to the eighth-grade students of SMP Negeri 5 Hulu Gurung.